Clinicophysiological and haematobiochemical effects of dexmedetomidinepropofol-sevoflurane anaesthesia in dogs - BISHT, DEVENDER SINGH; JADON, NARENDRA SINGH; BODH, DEEPTI; KANDPAL, MANJUL (The Indian Journal of Animal Sciences, 2018)
The present study was conducted to evaluate the clinicophysiological and haematobiochemical effects of dexmedetomidine in dogs undergoing propofol-sevoflurane anaesthesia. Twelve apparently healthy adult dogs were divided into two groups having 6 animals each. Animals of group I received atropine sulphate @ 0.04 mg/kg s.c. + dexmedetomidine @ 10 μg/kg i.v. while animals of group II were administered atropine sulphate @ 0.04 mg/ kg s.c. + dexmedetomidine @ 15 μg/kg i.v. Anaesthesia was induced with propofol (as i.v. bolus till effect) and maintained with sevoflurane. Clinicophysiological and haematobiochemical parameters were recorded at different intervals. Quicker attenuation of clinical reflexes was observed in both groups. Induction time was significantly lower while duration of anaesthesia, recovery time, standing time, complete recovery time and percent reduction in MAC of sevoflurane was significantly higher in group II. Non-significant differences in induction dose of propofol, physiological and haematobiochemical parameters were observed in both groups. Significant decrease in heart rate, respiration rate, rectal temperature, haemoglobin oxygen saturation and significant increase in mean arterial pressure was recorded in both the groups. Transient significant decrease in haemoglobin, total leukocyte count, total erythrocyte count and transient significant increase in glucose, urea nitrogen, creatinine, alanine aminotransferase, aspartate aminotransferase and cortisol was recorded in both the groups. Erythrocyte sedimentation rate increased significantly while insulin level decreased significantly in both groups. Both anaesthetic combinations used in the present study produced satisfactory anaesthesia and muscle relaxation, therefore can be suggested for clinical use in canine patients undergoing propofol-sevoflurane anaesthesia.